2022
DOI: 10.14202/vetworld.2022.1430-1437
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological perspective associated with principal risk factors of Trichinella spiralis infection in pigs and humans in Egypt

Abstract: Background and Aim: In Egypt, there is a scarcity of recent data on trichinellosis in pigs and humans. Therefore, this study aimed to determine the epidemiological profile and risk factors associated with Trichinella spiralis infection as well as to assess the effectiveness of the trichinoscope and digestion technique in diagnosing trichinellosis. Materials and Methods: Data were collected on 33812 pigs slaughtered during a year at the Al-Basateen abattoir, Cairo Governorate, Egypt. The slaughtered pigs had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…Pork is the most common source of human trichinellosis, which can cause clinical symptoms such as myalgia, diarrhea, fever, facial edema, and headaches, and may even be fatal [ 33 ]. Trichinella spiralis is the only species reported in Egypt so far [ 32 ], and it has been identified in pigs [ 34 , 35 ], rodents [ 36 ], and dogs [ 34 , 37 ]. In Egypt, the reported infection rate in slaughtered pigs and pork products ranges from 0% to 6% [ 19 , 35 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pork is the most common source of human trichinellosis, which can cause clinical symptoms such as myalgia, diarrhea, fever, facial edema, and headaches, and may even be fatal [ 33 ]. Trichinella spiralis is the only species reported in Egypt so far [ 32 ], and it has been identified in pigs [ 34 , 35 ], rodents [ 36 ], and dogs [ 34 , 37 ]. In Egypt, the reported infection rate in slaughtered pigs and pork products ranges from 0% to 6% [ 19 , 35 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trichinella spiralis is the only species reported in Egypt so far [ 32 ], and it has been identified in pigs [ 34 , 35 ], rodents [ 36 ], and dogs [ 34 , 37 ]. In Egypt, the reported infection rate in slaughtered pigs and pork products ranges from 0% to 6% [ 19 , 35 , 38 , 39 , 40 , 41 ]. Only one old report on the seroprevalence of Trichinella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Trichinella infections, seasonal fluctuations were also reported in different regions of the world. Climate changes with increasing temperatures and reduction of environmental humidity significantly altered the biology of both the parasitic larvae and susceptible host species [ 39 , 45 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, T. spiralis has also been identified in rodents [ 37 ] and in dogs [ 38 ] in different Egyptian regions. Additionally in humans, the seroprevalence rate of T. spiralis (IgG) was 10% (9/90) [ 39 ], and 60.9% (56/92) [ 40 ] in the examined humans that were linked to the consumption of pork in Egypt. Similarly to Egypt, there are scarce reports on the existence of Trichinella spp., either in camels or other animal species.…”
Section: Introductionmentioning
confidence: 99%
“…The previous finding was reported almost 15 years ago and, since this time, no further studies were performed to confirm the association between pigs and HEV infection in Egypt. However, the number of pig abattoirs has been increasing in recent years in Egypt and recent studies have reported that pigs could be a source of infections for Trichinella spiralis and Brucella suis in humans [99,100].…”
Section: Pigsmentioning
confidence: 99%